2022
DOI: 10.1021/acsami.2c12890
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Tri-switchable Wettability Surface for Versatile Droplet Manipulations

Abstract: Smart surfaces with tunable wettability are promising due to their abilities to create diversified functionalities that the fixed surfaces cannot provide. However, limited by imprecise adjustment of structural geometry and almost conventional switching modes of wettability, it is still challenging to achieve the reversible switching between multiple wetting states. Herein, a novel tri-switchable wettability surface with an in situ switching ability is used for the manipulation of a given droplet, which consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Apart from the aforementioned stimuli, other external stimuli, including stress [233,234], solvent [235,236], and electric field [237][238][239], can also be used to trigger the dynamic behaviors of intelligent stimulus-responsive structures manufactured by FsLDW technology. For instance, Gräf et al demonstrated the mechanically sensitive surface structural color of LIPSS-based diffraction gratings on ductile austenitic stainless steel through FsLDW.…”
Section: Other Stimulus-responsive Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the aforementioned stimuli, other external stimuli, including stress [233,234], solvent [235,236], and electric field [237][238][239], can also be used to trigger the dynamic behaviors of intelligent stimulus-responsive structures manufactured by FsLDW technology. For instance, Gräf et al demonstrated the mechanically sensitive surface structural color of LIPSS-based diffraction gratings on ductile austenitic stainless steel through FsLDW.…”
Section: Other Stimulus-responsive Structuresmentioning
confidence: 99%
“…Once the increasing tensile force made the microcolumn spacing larger than the droplet diameter, the droplet would completely contact the substrate, thus making the surface present rosepetal-like high adhesion. Therefore, by controlling the uniaxial tensile stress, the reversible switching of triple controllable wettability characteristics could be realized flexibly (figure 17(h)) [234].…”
Section: Multifunctional Surfacesmentioning
confidence: 99%
“…In sharp contrast to the dry adhesion mechanism, mussels secrete specialized proteins, known as catecholic amino 3, 4-dihydroxyl- l -phenylalanine (DOPA), for clinging to wet surfaces. , The DOPA and its derivatives have demonstrated extraordinarily strong interfacial adhesions as a natural adhesive. Inspired by these biological adhesion mechanisms, numerous artificial architectures and adhesive materials with switchable adhesion performances have been reported. The biomimetic materials have potential applications in smart-printing systems, industrial assembly and manipulation systems, and medical adhesives. However, it remains an enormous challenge to allow the insect-inspired microstructures to interlock with flat surfaces, while the gecko-inspired hierarchical structures suffer from complex manufacturing processes and poor mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…In another paradigm, Song et al presented a stretchable DSM actuator by seeding the magnetic microcolumn array on elastic polydimethylsiloxane platform, where the selective capture/release over droplets could be readily realized through tuning the grasping gaps of adjacent microcolumn arrays upon mechanical stretch. [17] More recently, Jing et al prepared a magneto-driven DSM actuator consisting of magnetic Fe-doped soft micropillars, which enables the droplets to move in a planar direction and especially release depending on the swinging inertia force. [18] Although ceaseless endeavors have been dedicated to the droplet actuators, several blockages have arisen DOI: 10.1002/aisy.202300375 Spatial manipulation of liquid droplets holds great significance in various areas from laboratory research to everyday life.…”
Section: Introductionmentioning
confidence: 99%
“…[ 16 ] 2) The repeated mechanical stretching would initiate poor longevity and deteriorate the steering performance. [ 17 ] 3) The magnetic release of droplets is highly dependent on the swinging cycles, the swinging angles as well as the swinging velocity, resulting in a complex and time‐consuming operation. [ 18 ] As a result, developing a robust, sensitive, and swing‐independent droplets‐spatial manipulator is highly desirable yet challenging to date.…”
Section: Introductionmentioning
confidence: 99%